Transport Corridor Planning for Zaria Road using Bus Rapid Transit Approach - Abubakar Isyaku Ismail; Isah Musa; Lawan Kamiludeen Abba (International Journal of Sustainable Engineering Innovations, 2025)
Background of study: Kano Metropolis is experiencing rapid urban growth, creating an urgent need for a modern and efficient urban transport system. Among its key corridors, Zaria Road has emerged as a promising candidate for development using a Bus Rapid Transit (BRT) model to address the challenges posed by current informal and inefficient transportation modes. Aims and scope of paper: This study assesses the feasibility of BRT implementation on Zaria Road by examining traffic patterns, passenger flow, and key traffic nodes, leading to infrastructure and design recommendations. Methods: A mixed-method approach combined field surveys, traffic and passenger counts, questionnaires, and stakeholder interviews with secondary data from recent literature. The analysis used both descriptive and inferential statistics. Result: Public transport on Zaria Road is largely informal, with 65% of operators unlicensed. Tricycles dominate at 67%, averaging 37,198 daily—far surpassing buses and taxis. Peak hours (5–6 a.m. and 9–10 a.m.) see up to 18,960 passengers, mainly commuting from residential areas to key hubs like motor parks, markets, and hospitals. Conclusion: Zaria Road's 90-meter right of way and high passenger demand make it well-suited for BRT development. A 15.9 km corridor with 54 proposed stops is recommended, supported by public-private partnerships and tricycle restrictions to ensure success.